2015
DOI: 10.1175/jcli-d-14-00622.1
|View full text |Cite
|
Sign up to set email alerts
|

Processes Leading to Double Intertropical Convergence Zone Bias in CESM1/CAM5

Abstract: The double intertropical convergence zone (ITCZ) bias in the eastern Pacific in the Community Earth System Model version 1 with Community Atmosphere Model version 5 (CESM1/CAM5) is diagnosed. In CAM5 standalone, the northern ITCZ is associated with inertial instability and the southern ITCZ is thermally forced. After air-sea coupling, the processes on both hemispheres are switched because the spatial pattern of sea surface temperature (SST) is changed.Biases occur during boreal spring in both CAM5 and the ocea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 52 publications
4
18
0
Order By: Relevance
“…Similarly, Song and Zhang () attribute the initial bias development to excessive downwelling shortwave radiation. Other studies suggest the double‐ITCZ bias arises because of uncertainty in the entrainment rate leading to deep convection that is too insensitive to large scale subsidence (Hirota et al, ), insufficient rain re‐evaporation within the deep convection parameterization leading to overly strong coupling between the boundary layer and deep convection (Bacmeister et al, ), or overly strong shallow convection leading to an overly moist boundary layer (Wang et al, ).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, Song and Zhang () attribute the initial bias development to excessive downwelling shortwave radiation. Other studies suggest the double‐ITCZ bias arises because of uncertainty in the entrainment rate leading to deep convection that is too insensitive to large scale subsidence (Hirota et al, ), insufficient rain re‐evaporation within the deep convection parameterization leading to overly strong coupling between the boundary layer and deep convection (Bacmeister et al, ), or overly strong shallow convection leading to an overly moist boundary layer (Wang et al, ).…”
Section: Introductionsupporting
confidence: 90%
“…More recent studies have expanded on the role of cloud and convective parameterizations in the development of the double‐ITCZ bias. Many of these studies suggest the double‐ITCZ bias results from deep convection parameterizations being too sensitive to SSTs and too insensitive to inhibitive large‐scale dynamic forcings (Hirota et al, ; Oueslati & Bellon, ; Song & Zhang, ; Wang et al, ). The enhanced sensitivity of convection to SST supports a coupled feedback cycle which can amplify otherwise small biases (Zhang et al, ), leading to the development of a double‐ITCZ within the first year of integration (Liu et al, ).…”
Section: Introductionmentioning
confidence: 96%
“…A double-ITCZ bias in CGCMs can emerge from several factors, such as the choice of convective parameterization scheme (Hirota et al, 2011), convective mixing (Möbis & Stevens, 2012;Song & Zhang, 2018), or from atmospheric transient eddies (Xiang et al, 2018). Additionally, a precipitation bias in CGCM simulations can emerge due to biases in tropical SST pattern associated with ocean current in the model itself (Wang et al, 2015). Indeed, Hwang and Frierson (2013) have shown that biases in cross-equatorial energy transport are linked to precipitation biases south of the equator.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse sensitivities of the double‐ITCZ and cold tongue biases to southeast Pacific low cloud fraction prompted investigation into other local processes, particularly the role of excessive convective activity and its relationship with local SSTs (e.g., Hirota et al, ; Oueslati & Bellon, ; Song & Zhang, ; Wang et al, ). Biases in simulated convective activity can amplify via coupled feedbacks (Zhang et al, ; Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This result may be driven by local improvement or by improvements in the meridional gradient of SST which has been shown to be important in determining ITCZ structure in idealized experiments (Neale & Hoskins, ). Further sensitivity studies have suggested processes controlling boundary layer humidity are important for the ITCZ as moister boundary layers favor triggering of deep convection (Bacmeister et al, ; de Szoeke et al, ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%